Sequestration of vacuum energy and the end of the universe - Kaloper, Nemanja; Padilla, Antonio (American Physical Society, 2015)
Recently, we proposed a mechanism for sequestering the standard model vacuum energy that predicts that the Universe will collapse. Here we present a simple mechanism for bringing about this collapse, employing a scalar field whose potential is linear and becomes negative, providing the negative energy density required to end the expansion. The slope of the potential is chosen to allow for the expansion to last until the current Hubble time, about 10 10 years, to accommodate our Universe. Crucially, this choice is technically natural due to a shift symmetry. Moreover, vacuum energy sequestering selects radiatively stable initial conditions for the collapse, which guarantee that immediately before the turnaround the Universe is dominated by the linear potential which drives an epoch of accelerated expansion for at least an e fold. Thus, a single, technically natural choice for the slope ensures that the collapse is imminent and is preceded by the current stage of cosmic acceleration, giving a new answer to the “why now?” problem.